Management of athlete achievement development, central java student sports coaching and training center - Nunuk Indah Winarni; Sugiharto Sugiharto; Andre Yogaswara (MEDIKORA, 2021)
One of the ways that the government restricts the development of regional elite sports is to seek to establish a variety of athlete development facilities. The purpose of this study is to determine and describe the implementation of performance development management for athletes in the Central Java Student Sports Development and Training Center (PPLOP). The research method uses explanatory research techniques. The research was conducted at the Central Java Student Physical Education and Training Center (BPPLOP). Research data sources are individuals directly related to PPLOP, including PPLOP athletes, athletes and other related party managers, coaches, and performance development coordinators. Techniques for collecting data through observations, interviews and documents. The results show that the performance management of PPLOP athletes in Central Java has achieved the best results in performance development, education, academic development and religious development. The process of improving PPLOP Central Java performance is correct, as evidenced by the performance of athletes in sports, science, and religion. The existence of the promotion and dismantling system has become a reference for the school and the PPLOP Center in Central Java to implement performance promotion management.Manajemen pembinaan prestasi atlet pemusatan pembinaan dan latihan olahraga pelajar Jawa Tengah  AbstrakSalah satu cara pemerintah dalam mengkondisikan pembinaan cabang olahraga unggulan di daerah adalah dengan mengupayakan berdirinya beberapa institusi pembinaan atlet. Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan implementasi manajemen pengembangan kinerja atlet di Pusat Pembinaan dan Latihan Olahraga Pelajar (PPLOP) Jawa Tengah. Metode penelitian menggunakan teknik explanatory research. Penelitian ini dilakukan di Balai Pemusatan Pendidikan dan Latihan Olahraga Pelajar (BPPLOP) Jawa Tengah. Sumber data penelitian adalah individu yang berhubungan langsung dengan PPLOP, antara lain pengurus, pelatih, koordinator pengembangan kinerja atlet PPLOP, atlet dan pihak terkait lainnya. Teknik pengumpulan data melalui observasi, wawancara, dan dokumen. Hasil penelitian menujukkan bahwa penerapan manajemen kinerja atlet PPLOP di Jawa Tengah mendapatkan prestasi terbaik dalam pengembangan kinerja, pendidikan, pengembangan akademik, dan pengembangan keagamaan. Proses peningkatan prestasi PPLOP Jawa Tengah sudah baik dan benar, terbukti dari prestasi para atlet di bidang olahraga, sains dan agama. Adanya sistem promosi dan degradasi menjadi acuan bagi pelaksanaan manajemen pembinaan prestasi di sekolah maupun di lingkungan Balai PPLOP Jawa Tengah.